Reclaiming the Silenced History of LGBTIQA+ Activism and the HIV/AIDS Crisis through Irish Theatre. An Interview with Phillip McMahon - J. Javier Torres-Fernández (Estudios Irlandeses, 2024)
The playwright and theatre director Phillip McMahon is also co-founder and co-director of THISISPOPBABY, a Dublin arts company founded in 2007 and said to have redefined modern Irish theatre, ripping up the space between popular culture, counterculture and high art. Their shows have played and toured around Ireland, the United Kingdom, Australia, and beyond. THISISPOPBABY voices queer culture on stage making space for the history and stories of the LGBTIQA+ Irish community positioning itself between performance and politics. The first play written by McMahon purely with LGBTIQA+ characters is Once Before I Go (2021), in which he explores and examines the legacy of the AIDS crisis in Irish queer lives. McMahon does not only voice the community’s historic pain, shame, and stigma, but he also foregrounds the fact that, despite marriage equality, the LGBTIQA+ rights movement has not come to an end. In fact, he claims that, after the COVID-19 pandemic, a wider society is ready to hear stories that have been long buried, forgotten, and suppressed.